Pincer Ruthenium Catalyzed Intramolecular Silylation of C(sp2)–H Bonds - Fang, Huaquan; He, Qiaoxing; Liu, Guixia; Huang, Zheng (Synlett, 2017)
Reported herein is a highly efficient intramolecular silylation of aromatic C–H bonds catalyzed by a pincer ruthenium complex, giving benzoxasiloles under relatively mild reaction conditions with broad substrate scope and low catalyst loadings. The silylation product can be further converted into a biaryl product by Pd-catalyzed Hiyama–Denmark cross-coupling reactions.
Keywords: C–H bond functionalization; silylation; ruthenium; pincer ligand; C–C coupling